The return of Baal to the Holy Land: Canaanite reconstructionism among contemporary Israeli Pagans - Feraro, Shai (Nova religio, 2016)
This article focuses on the recent emergence of Canaanite Reconstructionism in Israel - a miniature movement within the country’s small, but growing, Pagan community. The discourse of Israeli adherents of Canaanite Reconstructionism regarding its links to ancient Canaanite culture and the land - indeed the very soil - of modern-day Israel is highlighted. The development of Israeli Canaanite Reconstructionism is examined in relation to the unique nature of Israeli society and identity politics, as well as to Canaanism, a cultural and ideological movement that climaxed during the 1940s in British Mandate Palestine but declined after the founding of the State of Israel in 1948.